Synchronizing the Destructions of the Mycenaean Palaces (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
These are the proceedings of the workshop "Synchronizing the Destructions of the Mycenaean Palaces" held at the Austrian Academy of Sciences. The contributions treat the chronologies of all important Mycenaean palatial complexes as well as of other coeval settlements in Greece and the Near East, thus providing the necessary preconditions for all kinds of fundamental historical studies on Mycenaean Greece during the palatial period.